The Role of Minority Stressors in Digital Dating Abuse Victimization and Perpetration among Sexual Minority Men - Yang, Jackie (Journal of interpersonal violence, 2023)
Digital dating abuse (DDA), a manifestation of intimate partner violence (IPV), is becoming more relevant. Despite elevated rates of IPV among sexual minority individuals and increased experiences of DDA, research has focused largely on face-to-face forms of IPV (e.g., physical assault) among presumed heterosexual couples. The minority stress theory offers a lens through which we can understand the elevated rates of IPV, including DDA, among sexual minority individuals. The purpose of this study was to explore the role of minority stressors in DDA victimization and perpetration among sexual minority men. A sample of 491 cisgender gay and bisexual men (Mage = 31.35, SDage = 11.60) was recruited online. Consistent with prior research, discrimination was associated positively with internalized homophobia (IHP). Discrimination and IHP were directly linked to DDA victimization and perpetration. Indirect effect from discrimination to DDA victimization and perpetration, mediated by IHP, were significant. This study highlights the relationship between minority stressors and DDA among sexual minority men and indicates the need for more work on DDA among marginalized groups including sexual and gender minorities.